Particulate carbon and nitrogen dynamics in a headwater catchment in Northern Thailand: hysteresis, high yields, and hot spots. Issue 19 (6th June 2016) - Ziegler, Alan D.; Benner, Shawn G.; Kunkel, Melvin L.; Phang, Valerie X.H.; Lupascu, Massimo; Tantasirin, Chatchai
Abstract: Rivers of South and Southeast Asia disgorge large suspended sediment loads, reflecting exceptionally high rates of erosion promoted by natural processes (tectonic and climatic) and anthropogenic (land‐use change) activities that are characteristic of the region. While particulate carbon and nitrogen fluxes have been characterized in some large Asian rivers, less is known about the headwater systems where much sediment and organic material are initially mobilized. This study, conducted in the 74‐km 2 Mae Sa Experimental Catchment in northern Thailand, shows that the Sa River is an important source for particulate organic carbon (POC) and particulate organic nitrogen (PON) transported to larger river systems and downstream reservoirs. However, the yields during three years of investigation varied greatly: 5.0–22.3 Mg POC km −2 y −1 and 0.48–2.02 Mg PON km −2 y −1 . The 22.3 Mg POC km −2 y −1 yield is the highest reported for any river on the Asian continent. Stream samples collected during 12 storms showed that almost 3% of the total suspended solid load is POC 0.7 µm to 2.0 mm in size. This percentage is higher than other values for most large rivers on the continent. Further, we documented a strong pulse hysteretic behaviour in the stream, whereby peak fluxes of POC and PON are often delayed (anticlockwise hysteresis) or accelerated (clockwise hysteresis) relative to stream flow peaks (or are complex), complicating the prediction of storm‐based or annual particulate carbon and nitrogen fluxes. Stream turbidity and total suspended sediment are reasonable proxies for POC and PON concentrations, while stream discharge is not a good predictor variable. Observed C:N ratios for measured particulate samples range from 3 to 83, with the high‐end values likely associated with fresh (non‐decomposed) vegetative material greater than 2 mm in diameter. The C:N ratio (weighted based on three sediment sizes) for 12 events ranges from 7.5 to 15.3. These modest values reflect the relatively low C:N ratios for small size fractions (0.7–0.63 µm) that comprise 50–90% of the TSS load in the events. Overall, organic material <0.63 µm contribute about 75% of the total POC load and 80% of the PON load. The annual C:N ratio for the river is approximately 10–11. Collectively, our findings indicate the occasionally high yields make the Sa River—and potentially other similar headwater rivers—a hot spot for POC and PON transported to downstream water bodies. Complex hysteresis patterns and high year‐to‐year variability hinders our ability to calculate and predict these yields without continuous, automated monitoring of discharge and turbidity. Copyright © 2016 John Wiley & Sons, Ltd.